(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2026)
This study explored integrating ethical leadership and sustainable secondary education administration in Anambra State. It aims to examine the relationship between ethical leadership (leadership integrity and accountability) and sustainable secondary education administration. The study adopted correlational research design. Two research questions and two hypotheses guided the study. The population for this study consisted of 257 principals in 257 public senior secondary schools in Anambra State. The sample size used for this study was 257 respondents, representing 100% of the entire population using census sampling technique. The instruments for data collection are two selfstructured questionnaires titled “Integrating Ethical Leadership Questionnaire “(IELQ) and Sustainable Secondary Education Administration Questionnaire (SSEAQ) with 40 items. A sample of 30 principals who share the same characteristics were drawn from Imo State for the reliability test. The reliability coefficient of integrating ethical leadership was .84 and sustainable secondary education Administration was .87 while leadership integrity was .86 and leadership accountability was .76 respectively using Cronbach method. Out of 257 copies of the questionnaire administered, 250 copies were properly filled out and retrieved, which represented 97.5% success. The research questions were answered using Pearson product moment correlation (r) statistics, while z-ratio was used to test the hypotheses at 0.05 level of significance. The study revealed that leadership integrity and leadership accountability are the components of integrating ethical leadership and there is a high positive relationship between integrating ethical leadershipand sustainable secondary education administration in Anambra State. It was recommended that principals in public senior secondary schools in Anambra State should encourage the use of leadership integrity and accountability for sustainable secondary education administration in Anambra State.